Behavioral interventions in schools : evidence-based positive strategies - Little, Steven G.; Akin-Little, Angeleque (Applying psychology in the schools book series., 2019)
"As rates of Autism Spectrum Disorder (ASD) diagnoses continue to rise, the need for evidence-based classroom interventions has never been greater. This fully updated text shows psychologists how to assess and implement interventions that target students with ASD and other mental health disorders. Contributors also describe how to use cognitive behavior therapy to treat a variety of symptoms and behaviors. This book provides school psychologists, counselors, social workers, administrators, and teachers with the tools they need to succeed in today's classroom"--